Bemerkungen zu neueren chronostratigraphischen Daten zum Verhältnis glazialer und pluvialer Klimabedingungen - Heine, Klaus (ERDKUNDE, 1974)
An attempt is made to set up relationships between glacial and pluvial climatic conditions, using as a basis available detailed chronostratigraphies from various parts of the world, especially the tropics and subtropics. Glacial periods in the tropics during the late Pleistocene correspond to arid and coal climatic conditions in subtropical areas. Pluvial periods in the subtropics were characterised by relatively short but pronounced climatic changes which occured from about 13,500 years ago. It appears that climatic changes of a thermal character happen with a worldwide ± synchronisation, but that climatic changes of hygral character happen at different times in different climatic zones. Glacial and pluvial climatic evidence is not therefore suitable for use in stratigraphic correlation.